Asiatic Lion: Ecology, Economics, and Politics of Conservation - Jhala, Yadvendradev V.; Banerjee, Kausik; Chakrabarti, Stotra; Basu, Parabita; Singh, Kartikeya; Dave, Chittaranjan; Gogoi, Keshab (Frontiers in Ecology and Evolution, 2019)
Asiatic lions typify most challenges faced by large carnivores: single population, historical bottlenecks, habitat loss, poaching, and conflict with humans. Their recovery from <50 in a few hundred km2 to >500 occupying 13,000 km2 of agro-pastoral Saurashtra landscape, Gujarat, India is an enigma. We review and evaluate the multidisciplinary aspects of lion conservation-strategy that covers ecology, conflict, community perceptions, economics, management, and politics. The history of modern lions in India dates back to 4-6,000 BP, but evidence suggests presence as early as 10-15,000 BP. Asiatic lions can be distinguished from African lions by their belly-folds; adult males and females weighing 160(±5) and 116(±4) kg respectively. Lion density ranged from 2-15/100 km2 in the Saurashtra landscape. Demographic parameters of Asiatic lions were comparable to African lions. Prides were related females and cubs; males lived separately in hierarchical coalitions having overlapping ranges with multiple prides. Lionesses mated with multiple coalitions to reduce infanticide and enhance genetic diversity of their progeny. Few hectares of scrub sufficed as daytime refuges, while >4 km2 patches were required for breeding. Sink populations outside Gir Protected Area (PA) were maintained by immigrants. Lions within PA fed primarily on wild-prey, while scavenging and predation on livestock was the mainstay outside. Monetary compensation for livestock-depredation, legal-protection, lion-related profits, combined with religious and cultural sentiments were major drivers of population recovery. The lion has become a socio-political instrument in Gujarat, which despite a Supreme Court directive, has not parted with founders to establish another population. Threats from epidemics loom large and currently a canine distemper virus outbreak is prevalent. Attacks on humans were rare, however, with increasing lion density the intensity of conflict is increasing. This, coupled with lowered tolerance of communities due to erosion of traditional values sets the stage for retaliation. Future of lions outside PA is uncertain as breeding refuges and their connecting corridors are vanishing rapidly. A human-free National Park of 1000 km2 is essential for ensuring a viable population that retains its ecological role and evolutionary potential. Legalising lion based ecotourism by forming village consortia holds promise to prevent land conversion and promoting lion-human coexistence.